Analysis of restriction fragment length polymorphism for the HLA-DR gene in Japanese patients with sarcoidosis. - Kunikane, H. (1994)
BACKGROUND--It is commonly assumed that some immunological disorder may play a part in the pathogenesis of sarcoidosis. Previous studies by several groups have shown a significant association with HLA-DR antigens in patients with sarcoidosis. In this study, restriction fragment length polymorphism (RFLP) analysis of the HLA-DR gene was designed to confirm the association at the gene level and to look for a gene rearrangement which may influence susceptibility to sarcoidosis. METHODS--Thirty two unrelated Japanese patients with sarcoidosis were tested for HLA antigens and subjected to RFLP analysis after digestion with Eco RI, Pst I, Bam HI, Pvu II, and Hind III by using an HLA-DR beta cDNA probe. A group of 47 unrelated healthy Japanese subjects served as controls. Frequencies of each restriction fragment were compared between the patients and the control subjects. Correlation between fragment frequencies and clinical features were also analysed. RESULTS--No restriction fragments of HLA-DR beta gene were found specific to the patients with sarcoidosis. The RFLP analysis could detect polymorphism of HLA-DR beta genes that was not distinguishable by conventional serological methods. Several restriction fragments of the DR beta gene were seen only in DRw52 positive individuals, and showed higher frequencies in the patients than in control subjects. The patients with these DNA fragments were likely to have limited stage disease with no ophthalmic involvement. CONCLUSIONS--An association between HLA and sarcoidosis was noted at the DNA level, although no restriction fragments were specific for this disease. RFLP analysis of the HLA gene is a more useful method than the usual HLA typing, and should be the first step in identifying the gene sequence which is connected with susceptibility to sarcoidosis.